Web usability testing on diabetic retinopathy consultation system - Rahim, Sarni Suhaila; Dolhalit, Mohamad Lutfi; A’bas, Nurul Najihah; Parumo, Shahril; Saifudin, Wan Sazli Nasaruddin; Abdullasim, Nazreen; Raja Omar, Raja Norliza; Md Khair, Siti Zakiah; Kalaichelvam, Khavigpriyaa; Noor Izhar, Syazwan Izzat (International Information and Engineering Technology Association, 2021)
This article presents an investigation on the usability testing of Diabetic Retinopathy Consultation System (DRCS) development. DRCS is an interactive medical web-based consultation system for diabetic retinopathy screening with the features of image processing and image editing. The expected outcome of this paper is a comprehensive analysis of the web usability towards the development of a novel consultation system for diabetic retinopathy screening. Seven important usability evaluation components were included in this testing in order to investigate the user engagement and satisfaction of the proposed medical consultation system. Online questionnaires were distributed as a method to collect user testing outputs. A total of 27 respondents from the health clinics were involved in this survey. According to the outcomes of the online survey, the majority of respondents are satisfied with the outcomes of the DRCS. In conclusion, the online findings depict that the DRCS is highly functional, as required by the target users to assist consultation among medical doctors on diabetic retinopathy screening. This system is expected to contribute to diabetic retinopathy screening management and produce a great usability to the users.